2002
DOI: 10.1117/1.1483316
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the spatial distribution of polarized light backscattered from layered scattering media

Abstract: The scattering of polarized light from a two layer scattering medium is investigated using Monte Carlo simulations. First order and normalized second order moments are used to analyze the spatial properties of the emerging light in different polarization states. Linearly and circularly polarized illumination is used to probe different depths. Absorption and layer thickness are varied and it is demonstrated that the determination of these values is aided by the inclusion of polarization information. The lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…Polarization memory results in a higher percentage of co-polarized light returning to the surface and a greater depth until polarization is randomized for circularly polarized incident light [15,16]. However, it was apparently that neither of these conditions was present in our experiments.…”
Section: Effects Of Circularly Polarized Lightcontrasting
confidence: 50%
“…Polarization memory results in a higher percentage of co-polarized light returning to the surface and a greater depth until polarization is randomized for circularly polarized incident light [15,16]. However, it was apparently that neither of these conditions was present in our experiments.…”
Section: Effects Of Circularly Polarized Lightcontrasting
confidence: 50%
“…9, by subtracting the cross-linear channel, measuring the multiple scattered (or totally depolarized) part of the signal, from the images obtained under copolarized channels, one obtains a good approximation of the polarization maintaining images, free from surface reflections if elliptical polarization is considered.…”
Section: Polarization Gatingmentioning
confidence: 99%
“…This method assumes that the amount of multiply scattered photons is the same for the linearly and elliptically polarized light. This assumption was previously evaluated using Monte Carlo simulations and it was determined that cross-linear polarized light is a good approximation for multiple-scattered circular polarized illumination [36]. …”
Section: Polarization Gatingmentioning
confidence: 99%
“…Here, we explore the feasibility of such system that is based on the property of circular polarized light to maintain its polarization in highly scattering media at larger depths as compared to linearly polarized light due to the so called circular "polarization memory" effect [34,35] Circularly polarized light undergos small-angle, forward scattering events in diffusely scattering media with Mie scatterers that are characterized by a predominately forward scattering phase function that largely preserves helicity for long distances in a turbid medium [22,34,36]. Furthermore, it was recently demonstrated that elliptically polarized light can be used to image scattering phantoms and biological tissue at different depths by varying the degree of ellipticity from linear to circular polarization [37].…”
Section: Introductionmentioning
confidence: 99%